MAPPING THE ECONOMIC IMPACT OF HALAL TOURISM IN INDONESIA: A SYSTEMATIC REVIEW AND BIBLIOMETRIC ANALYSIS (2019–2025) - Rafika Amira; Feri Ferdian (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Research Aims: This study aims to map the scientific development and analyze the economic impact of halal tourism in Indonesia by conducting a systematic review and bibliometric analysis of scholarly publications from 2019 to 2025. Design/methodology/approach: This research employs a quantitative bibliometric approach integrated with a systematic literature review (SLR). Data were sourced from the Scopus database using the keywords “halal tourism” AND “economic impact”. A total of 26 relevant documents were analyzed using VOSviewer and Biblioshiny to explore publication trends, keyword co-occurrence, author collaboration, citation influence, and thematic clustering. Research Findings: The findings reveal that “halal tourism” is a central theme in the literature, frequently associated with keywords such as “Indonesia,” “sustainability,” and “economic development.” The annual publication growth rate reached 38.31%, with research activity dominated by Indonesian scholars. Two primary thematic clusters were identified: one focused on destination experiences and the other on adaptive capacity and policy analysis. However, empirical investigations into the economic impact of halal tourism remain limited and are often overshadowed by normative or ethical discussions. Theoretical Contribution/Originality: This study contributes to the academic literature by offering a comprehensive map of research patterns in halal tourism, particularly its economic dimensions. It is one of the first bibliometric studies to focus exclusively on Indonesia, highlighting the intellectual structure, gaps, and opportunities within the field. The results provide valuable insights for future researchers, policymakers, and tourism stakeholders seeking to advance halal tourism as part of Indonesia’s sustainable development agenda.